Management of chronic refractory cough in adults - Visca, Dina (Eur J Intern Med, 2020)
Cough is a common respiratory symptom that is considered to be chronic when it lasts more than eight weeks. When severe, chronic cough may significantly impact an individual's quality of life, and such patients are frequently referred for specialist evaluation. Current international guidelines provide algorithms for the management of chronic cough: in most cases, treatment of the underlying disease is sufficient to improve or resolve cough symptoms. Severe chronic cough may significantly affect patients' quality of life and necessitate frequent referral for specialist evaluations. In this narrative review, we summarize non-pharmacologic and pharmacologic management of adult patients with chronic cough of known cause that persists after proper treatment (chronic refractory cough, CRC) or chronic cough of unknown cause in adult patients. If chronic cough persists even after treatment of the underlying disease, or if the chronic cough is not attributable to any cause, then a symptomatic approach with neuromodulators may be considered, with gabapentin as the first choice, and opioids or macrolides as alternatives. Speech pathology treatment and/or neuromodulators should be discussed with patients and alternative options carefully considered, taking into account risk/benefit. Novel promising drugs are under investigation (e.g. P2×3 inhibitors), but additional studies are needed in this field. Speech pathology can be combined with a neuromodulator to give an enhanced treatment response of longer duration suggesting that non-pharmacologic treatment may play a key role in the management of CRC.